Rapid ventricular pacing during transcatheter valve procedures using an internal device and programmer: A demonstration of feasibility. Issue 5 (20th August 2019) - Jones, Brandon M.; Jobanputra, Yash; Krishnaswamy, Amar; Mick, Stephanie; Bhargava, Mandeep; Wilkoff, Bruce L.; Kapadia, Samir R.
Abstract: Objectives: To develop a protocol for using a pre‐existing, permanent pacemaker or defibrillator device for rapid ventricular pacing during transcatheter valve procedures and demonstrate feasibility. Background: Placement of a passive fixation, temporary pacemaker wire is considered routine during most transcatheter valve procedures to facilitate controlled or rapid ventricular pacing at the time of balloon expansion or valve deployment. Many patients presenting for such procedures have a pre‐existing, permanent pacemaker or defibrillator device which could be used for the same function, obviating the need for temporary pacemaker wire placement. Methods: We developed a strategy for rapid pacing from the pre‐existing device using a programmer during transcatheter valve procedures in consecutive patients over a 3‐month period. Complications and clinical outcomes were recorded. Results: There were 135 transcatheter valve procedures performed during the study. Of these, 28 (20.7%) had pre‐existing devices (17 transcatheter aortic valve replacement, 3 aortic valve‐in‐valve, 2 mitral valve‐in‐valve, and 6 balloon aortic valvuloplasty). All patients underwent rapid ventricular pacing using a commercially available device programmer. There were no adverse events related to device pacing and no patients required placement of a temporary pacemaker wire during the procedure. At 30‐days follow‐up, there were no deaths, one major vascular complication related to arterial access, and one patient with renal failure requiring dialysis. Conclusion: Pacing from a commercially available device programmer is safe, feasible, and may reduce both procedural cost and complications such as cardiac tamponade by avoiding placement of a temporary pacemaker lead during transcatheter valve procedures.